2018
DOI: 10.1055/s-0038-1673426
|View full text |Cite
|
Sign up to set email alerts
|

Oophoropexy to the Round Ligament after Recurrent Adnexal Torsion

Abstract: Recurrent adnexal torsion is a rare gynecological emergency. We report a case of recurrent ipsilateral adnexal torsion in a woman with polycystic ovaries, previously submitted to a laparoscopic plication of the utero-ovarian ligament. Due to the recurrence after the plication of the utero-ovarian ligament, the authors performed a laparoscopic oophoropexy to the round ligament, which is an underreported procedure. The patient was asymptomatic for 1 year, after which she had a new recurrence and needed a unilate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Several oophoropexy techniques have been reported, such as fixation of the ovary to the pelvic side wall, the posterior uterine wall, the sacro-uterine ligament, the posterior abdominal wall, and the ligamentum teres uteri both with and without plication of the utero-ovarian ligament [6, 10, 12, 19, 20]. The best management strategy of recurrent ovarian torsion is still under debate, and no clear answer exists regarding patient selection, timing, the preferred surgical method, and whether the procedure should be performed bilaterally or unilaterally [7, 17].…”
Section: Discussionmentioning
confidence: 99%
“…Several oophoropexy techniques have been reported, such as fixation of the ovary to the pelvic side wall, the posterior uterine wall, the sacro-uterine ligament, the posterior abdominal wall, and the ligamentum teres uteri both with and without plication of the utero-ovarian ligament [6, 10, 12, 19, 20]. The best management strategy of recurrent ovarian torsion is still under debate, and no clear answer exists regarding patient selection, timing, the preferred surgical method, and whether the procedure should be performed bilaterally or unilaterally [7, 17].…”
Section: Discussionmentioning
confidence: 99%
“…An ovary that was necrotic and hemorrhagic was found during anatomopathological analysis. Consequently, the patient exhibited no further signs of a recurrence of contralateral ovarian torsion [ 26 ].…”
Section: Ovarian Torsion In Polycystic Ovary Syndromementioning
confidence: 99%
“…Oophoropexy has been described as a preventive intervention to decrease the risk of recurrent torsion. Various techniques have been described, including plication of the utero-ovarian ligament, suturing the ovary to the round ligament or the posterior uterus, or pelvic sidewall [52][53][54]. Small studies have shown success with fertility and normal appearance of ovaries on follow-up ultrasound, but long-term effects of oophoropexy on recurrence rates and fertility are not known [52].…”
Section: Treatmentmentioning
confidence: 99%